Hydrogen and Oxygen Isotope Characteristics of Different Organs of Panax Notoginseng and its Relationship with Irrigation Water - LI Xinyue;LIANG Shewang;LI Dongxue;GUO Ting;ZHAO Huiyu;GUO Chunping;HE Zhongjun (Editorial Board of Journal of Isotopes, 2021)
Abstract: Analyze the characteristics, correlation and influencing factors of various organs (stems and leaves, reed heads, tubers, tendons, fibrous roots) of Panax notoginseng from different origins and stable hydrogen and oxygen isotopes in irrigation water, and provide technical support for whether it can be used as a traceability indicator of origin. In the Panax notoginseng production area—Jingxi Guangxi area, Wenshan Yunnan area, Yunnan new development area, 43 Spring Panax notoginseng plants and corresponding irrigation water were collected and their stable hydrogen and oxygen isotope ratios were determined. The latitude, longitude and altitude were measured on site, and carried out difference analysis and correlation analysis. The results show that the δD of each organ of Panax notoginseng conforms to the law of decreasing with the increase of altitude and latitude. The change law of δ18O is opposite to δD. The δD and δ18O values of various organs of Panax notoginseng have significant differences（P<0.05）, and the changing laws are different. The δ18O of the organs of Panax notoginseng has obvious regional characteristics, and the other organs except the tuber, tendons, and fibrous roots can be mutually predicted, and can be used as the origin traceability index. There is a very significant positive correlation between δD and δ18O in irrigation water in the Panax notoginseng production area, with obvious longitude, latitude, and elevation effects, but only the δD of reed head and irrigation water δD have a significant positive correlation. The results can provide a theoretical basis for the traceability of the origin of Panax notoginseng.